KAJIAN HARGA POKOK PRODUKSI PROTOTIPE BUAH KELAPA KECIL KUNING DENGAN SISTEM PEMBEBANAN BERBASIS AKTIVITAS DAN EFEKNYA TERHADAP HARGA JUAL DAN PERSEDIAAN - Wiryawan Suputra Gumi; I Nyoman Normal (Forum Manajemen STIMI Handayani Denpasar, 2013)
The aims of this research that relate for yellow small coconut fruitprototype were : (1) To calculate cost of good manufactured; (2) To determinecost price; and (3) To recognized ending inventory. The research results shew that: (1) Cost of good manufactured yellow small coconut fruit prototype according to UPT PSTKP Bali was Rp 26.553,31 each unit, that followed by raw materal cost Rp 11.379,99, direct labour cost Rp 7.586,66, variable ovrehead cost Rp 3.793,33,and ﬁ xed overhead cost Rp 3.793,33, but according to Activity Based Costing (ABC)systems was Rp 26.969,58 each unit, that followed Unit-Level Activity Cost Rp19.315,89, Batch-Related Activity Cost Rp 1.571,48, Product-Sustaining ActivityCost Rp 5.591,34, dan Facility-Sustaining Activity Cost Rp 490,86; (2) Selling priceyellow small coconut fruit prototype according to UPT PSTKP Bali was Rp 34.519,30each unit, that price formed by cost of good manufactured Rp 26.553,31 expectedproﬁ t margin Rp 5.310,66, and operation expense Rp 2.655,33 but according to fullcost pricing method, selling price was Rp 35.060,45 each unit, that price formed bycost of good manufactured Rp 26.969,58, expected proﬁ t margin Rp 5.393,92, andoperating expense Rp 2.696,96; and (3) Ending inventory yellow small coconut fruitprototype according to UPT PSTKP Bali was Rp 1.327.665,50, but according toFinancal Accounting Standard ending inventory was Rp 1.348.479,00. UPT PSTKPBali recognized and reported ending inventory smaller Rp 20.813,50. Financialstatement reported by UPT PSTKP Bali was understated.